Optimizing Texture Position for Improved Dynamic Stability and Operational Performance in two-lobe Journal Bearings (London Journal of Engineering Research, 2023)
This research paper presents a theoretical investigation into the optimization of texture position in two-lobe journal bearings using finite element method (FEM). Journal bearings play a vital role in various industrial applications by supporting rotating machinery and ensuring efficient operation. Surface texturing has emerged as a promising technique to enhance tribological performance by altering the hydrodynamic lubrication mechanisms. The present study is focused on the influence of texture position on dynamic stability and operational efficiency. Through the development of a comprehensive FEM model, the dynamic behavior of the bearing system is analyzed under varying texture positions. The effects of different texture locations on the dynamic coefficients, including stiffness and damping, are evaluated to understand their impact on stability and performance. Subsequently, the operational performance metrics, such as friction reduction and load-carrying capacity, are quantified. The optimization process involves systematic exploration of texture positions using numerical algorithms to identify the optimal configuration that maximizes dynamic stability and operational efficiency. The outcomes of this study provide insights into the intricate interplay between texture placement and the bearing's dynamic response, shedding light on the underlying mechanisms that lead to improved performance.
Keywords: two-lobe textured journal bearing; load carrying capacity; dynamic stability; critical mass of journal; threshold speed; whirl frequency ratio